STUDI ANALISIS TENTANG PELAKSANAAN PENDIDIKAN DI PESANTREN TAHFIZ AL-QUR'AN ANAK-ANAK YANBU' AL-QUR'AN KUDUS JAWA TENGAH - Ahmad Falah (Geneologi PAI: Jurnal Pendidikan Agama Islam, 2017)
The paper of research institutional traditional system (pesantren) for children age 6-12 Th in Yanbu' Al-Qur'an Kudu Central Java. The fist program is memorization of the Qur'an 30 Juz, and learning is basic school (MI) Madrasa Tahfiz al-Qur'an. Educational Islamic system in institutional traditional include of teacher, student (santri), materials or curriculum, methods of memorization of al-Qur'an, and insfastructure and environment education is dominant factor in succesfull system education especially in Pesantren.